Ocular manifestations of childhood malnutrition- an overview - Chandran, Rabindran; Gedam, D. Sharad (International Journal of Medical Research and Review, 2017)
Vitamin A deficiency is the commonest cause of preventable childhood blindness in developing countries. Severity of xerophthalmia is directly proportional to the severity of malnutrition.